IV/IT hUC-MSCs Infusion in RRMS and NMO: A 10-Year Follow-Up Study - Zhengjuan Lu; Zhengjuan Lu; Zhengjuan Lu; Zhengjuan Lu; Zhengjuan Lu; Lin Zhu; Lin Zhu; Lin Zhu; Lin Zhu; Lin Zhu; Zhuo Liu; Zhuo Liu; et al. (Frontiers in Neurology, 2020)
Background: Stem cell transplantation is emerging as a potential therapeutic strategy in several autoimmune diseases. However, the safety and feasibility of long-term combined intravenous (IV) and intrathecal (IT) administration of hUC-MSCs in relapse remitting multiple sclerosis (RRMS) and neuromyelitis optica (NMO) is largely unknown.Objectives: In this study, we followed up the long-term safety and feasibility of combined IV and IT human umbilical cord mesenchymal stem cells (hUC-MSCs) transplantation in patients with RRMS and NMO.Methods: Five NMO patients and 5 RRMS patients were treated intravenously (4 times) and intrathecally (3 times) over a 21-day period with low-dose allogeneic umbilical cord blood–derived MSCs. All of the patients were monitored regularly by an investigator in a blinded manner to access the Expanded Disability Status Scale, MRI characteristics, and adverse events every 3 months within 12 months and once every year thereafter for 10 years after transplantation.Results: During the long-term follow-up, our data suggested that combined IV and IT administration of hUC-MSCs transplantation is safe and feasible. None of the intolerant adverse events, such as tumor formation and peripheral organ/tissue disorders, were observed throughout the 10-year follow-up.Conclusions: These data suggest that combined intravenous and intrathecal low-dose hUC-MSCs transplantation is safe and feasible in RRMS and NMO patients in the long term. The conclusion requires confirmation by future clinical trials in a larger cohort.